Kerja Raya Jempol / Nur Aqilah Natasha Mohd Fadzli - Mohd Fadzli, Nur Aqilah Natasha (Faculty of Civil Engineering, 2018)
Industrial Training is a compulsory requirement for students in certain programs at all levels of higher education in Institutions of Higher Learning (IHL). To increase the level of graduates able to work, Industrial Training program was introduced to strengthen the competencies required. Industrial Training courses give students learning opportunities in the world of work to receive practical experience to improve the reliability of the market. Industrial Training refers to expose students to the real-life experiences of the engineering works and to get them involved in Civil Engineering projects before graduation. It is one of the requirements for the award of Diploma in Civil Engineering is that the student must complete at least eight (8) weeks of Industrial Training. Industrial Training is usually collected during the semester break at the end of the second year student (semester 4 and above). The technical and non-technical outcomes of the course may be assessed and evaluated through this Industrial Training.